Traumatic versus Non-Traumatic Spinal Cord Injury: Complications and Functional Outcomes in an Acute Inpatient Rehabilitation Hospital - Pereira, Patrícia (2025)
Introduction: This retrospective cohort study aimed to compare demographic differences, functional outcomes, duration of stay (DOS), and complication profiles between patients with traumatic (TSCI) and non-traumatic (NTSCI) spinal cord injuries in an acute inpatient rehabilitation service. Methods: This study included 128 spinal cord injury patients, 68 with traumatic and 60 with nontraumatic lesions, admitted to the Physical Medicine and Rehabilitation service of Hospital de Braga between January 2017 and December 2022. Parameters included demographics, injury causes, neurological levels, ASIA impairment scales, functional scores (FIM and SCIM), DOS, complications, discharge destination, bladder management, and ambulation level. Results: NTSCI patients were older (mean 64 vs 59 years, p=0.074) and predominantly female (45% vs 16.2%, p=0.000). TSCI was primarily caused by falls (66.2%), while NTSCI stemmed from degenerative diseases (50%). TSCI patients had significantly longer DOS (mean 65.07 vs 45.78 days, p=0.021) and were admitted later post-injury (mean 51.61 vs 26.77 days, p=0.001). NTSCI patients had more paraplegia (61.7%) and incomplete injuries, while TSCI showed higher rates of tetraplegia (72.1%) and complete injuries (AIS A, 27.7% vs 7.3%, p=0.010). TSCI patients experienced more complications (mean 2.0 vs 1.4 per patient), including higher rates of pressure ulcers and depressive symptoms (p<0.05). Functional outcomes at discharge (FIM and SCIM scores) were lower in TSCI but demonstrated significant intra-group improvements, with no intergroup differences in functional gains. NTSCI patients were more likely to be discharged home, walk with assistive devices, and manage bladder function, while TSCI patients frequently required wheelchairs and indwelling catheters. Conclusion: NTSCI patients were older, hospitalized earlier, had shorter rehabilitation DOS, fewer complications, and better functional status at admission than TSCI patients. Despite more severe impairments, TSCI patients achieved comparable functional gains during rehabilitation, emphasizing the need for tailored management strategies to address their higher complication rates and disability levels.